2015
DOI: 10.28945/2103
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Digital Lecture Halls: A Study of Student Course Engagement and Mobile Device use During Lecture

Abstract: Universities have experienced increases in technology ownership and usage amongst students entering undergraduate programs. Almost all students report owning a mobile phone and many students view laptops and tablets as educational tools, though they also report using them for nonacademic activities during lectures. We explored the relationship between student course engagement and the use of smartphones, laptops, cell phones, and tablets during lecture. Undergraduate students responded to an online survey aski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Our findings were to some extent less than the findings of Canada (93%) and the USA (80%). [44,45] Our respondents opined that their teachers encourage them to use smart devices; similar finding also reported from the UAE and USA [46,47] ; such corroboration was also witnessed even in medical schools. [48,49] The study respondents used a number of electronic devices, which was also observed among the US health-care professionals and four Canadian university students.…”
Section: |Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our findings were to some extent less than the findings of Canada (93%) and the USA (80%). [44,45] Our respondents opined that their teachers encourage them to use smart devices; similar finding also reported from the UAE and USA [46,47] ; such corroboration was also witnessed even in medical schools. [48,49] The study respondents used a number of electronic devices, which was also observed among the US health-care professionals and four Canadian university students.…”
Section: |Discussionsupporting
confidence: 79%
“…UniKL-RCMP medical students use a number of electronic devices, and many of them have and use more than one device: laptop (195, 85%), smartphones (203, 90%), tablet (78, 34%), and dongle (3, 1%). Thirty-seven percent (86), 34% (78), 19% (44), and 10% (22) of the study participants use smart devices for academic purpose for 1-2, 3-4, 44, and o1 h, respectively. Again, 35% (80), 28% (64), 29% (68), and 8 (18) of the study participants use smart devices for nonacademic purpose for 1-2, 3-4, 44, and o1 h, respectively ( Table 3).…”
Section: |Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lecturers have responded by adopting innovative pedagogical methods such as the use of mobile technology devices, including tablets, laptops and smartphones. Such devices have also been used regularly by university students in a variety of settings and have become the standard for note taking, recording, photographing work, and searching the Internet within the academic learning environment at university (Roberts & Rees, 2014;Witecki & Nonnecke, 2015). While students regard mobile devices as highly useful in such university contexts, ready access to the internet and social network sites (SNS) has changed the forms and depth of students' engagement in the teaching and learning process.…”
Section: Impact Change In Universitiesmentioning
confidence: 99%
“…There is considerable research literature that focuses on what students do with the technology used in class and the technology they are using (Norton, Sonnemann, & McGannon, 2013;Roberts & Rees, 2014;Witecki & Nonnecke, 2015); fewer studies address the amount of time spent by students in class connected to the Internet and utilising SNS unrelated to their academic work. This research study aims to help address this gap in the research literature while also reflecting on the impact of students' in-class behaviours and level of active participation in the teaching and learning environment.…”
mentioning
confidence: 99%